Impact of reading comprehension skills on school learning: A study made in a commune of the Metropolitan region, Chile - Núñez-Valdés, Karen (2019)
The acquisition of skills for reading comprehension is essential in today’s society, because it is not only a way of learning new contents, but also a necessary element to be inserted in life in society. In this article, we propose to investigate the impact of reading comprehension skills on the learning outcomes of fifth grade students from ten schools in a commune of the Metropolitan Region, Chile. A quantitative methodology was used. Data were analyzed through descriptive statistics, correlations, and hierarchies. It is intended to get a conclusion and to know the skills that have the greatest impact on the results obtained by the students in the tests indicated above and with that, to give guidelines for the strengthening of more realistic reading comprehension abilities.